2008
DOI: 10.15381/rpb.v15i2.1733
|View full text |Cite
|
Sign up to set email alerts
|

Efecto tóxico de Argemone subfusiformis Ownb. y Tagetes patula Link sobre larvas del IV estadio y pupas de Aedes aegypti L.

Abstract: IntroducciónLos mosquitos son los responsables de la transmisión bioló-gica de varias enfermedades consideradas de alta incidencia y en muchos casos mortales en países tropicales y subtropicales (Organización Mundial de la Salud, 1984, Organización Mundial de la Salud, 1985. Según la Organización Panamericana de la Salud (2008) el cambio climático, escasez de políticas públicas en salud, presupuestos regionales y nacionales restringidos así como la falta de una educación y reordenamiento ambiental, además de l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
0
9
0
4
Order By: Relevance
“…In the present study, the ingestion of maize leaves that were treated with 30% A. ochroleuca ethanolic extracts caused 31% mortality in S. frugiperda 3rd instar larvae until just before pupation. Vidal et al (2009) reported that lower concentration (20 to 154 mg/L) extracts from leaves of Argemone subfusiformis Ownbey (Papaveraceae) caused high mortality (90 to 100%) in the 4th instars of yellow fever mosquito, Aedes aegypti L. (Diptera: Culicidae), at 24 h post treatment. A field application of a 50% concentration of extracts from leaves of A. mexicana caused 90% mortality in adults of the stink bug Oebalus insularis (Stål) (Hemiptera: Pentatomidae) at 48 h after application (Cepero 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the ingestion of maize leaves that were treated with 30% A. ochroleuca ethanolic extracts caused 31% mortality in S. frugiperda 3rd instar larvae until just before pupation. Vidal et al (2009) reported that lower concentration (20 to 154 mg/L) extracts from leaves of Argemone subfusiformis Ownbey (Papaveraceae) caused high mortality (90 to 100%) in the 4th instars of yellow fever mosquito, Aedes aegypti L. (Diptera: Culicidae), at 24 h post treatment. A field application of a 50% concentration of extracts from leaves of A. mexicana caused 90% mortality in adults of the stink bug Oebalus insularis (Stål) (Hemiptera: Pentatomidae) at 48 h after application (Cepero 1994).…”
Section: Discussionmentioning
confidence: 99%
“…La especie se seleccionó debido a los antecedentes del género para el control de plagas (Russo et al, 2005;Camarillo et al, 2009;Vidal et al, 2009;Barajas et al, 2011;Espitia, 2011). Las hojas de huacatay se emplearon para la preparación de los extractos acuosos crudos.…”
Section: Materials Biológicounclassified
“…El huacatay puede ser usado como plaguicida, y se le atribuyen propiedades medicinales como digestivo, carminativo y antiabortivo (Vidal et al, 2009;Grados & Peláez, 2012;Murga-Gutierrez et al, 2012). La infusión de sus hojas se usa para aliviar los dolores gástricos, y la decocción de sus flores y hojas frescas para aliviar los catarros y bronquitis.…”
unclassified
“…Es importante realizar evaluaciones de plantas que han demostrado propiedades repelentes y manipular su presencia dentro de los cultivos, con el fin de alejar a S. p. purpurascens del cultivo principal. Entre las especies que se pueden evaluar se encuentran la higuerilla (Ricinus comunis L.) el ajo (Allium sativum L.) y el cempasúchil (Tagetes erecta L.) (Grainge y Ahmed, 1988;Rodríguez y Nieto, 1997;Vidal et al, 2008). Lo anterior permitiría tener áreas que concentren mayor diversidad de plantas con un propósito específico dentro del agroecosistema, con el fin de minimizar el daño que el saltamontes ocasiona al cultivo principal.…”
Section: Abundance Of S P Purpurascensunclassified
“…It is important to carry out assessments in plants that have demonstrated repellent properties and manipulate its presence within the crops, in order to push away S. p. purpurascens from the main crop. Among the species that can be evaluated are include castorbean (Ricinus communis L.), garlic (Allium sativum L.) and marigolds (Tagetes erecta L.) (Grainge and Ahmed, 1988;Rodríguez and Nieto, 1997;Vidal et al, 2008). This would allow having areas that concentrate a greater diversity of plants with a specific purpose within the agroecosystem, in order to minimize the damage that the grasshopper causes to the main crop.…”
Section: Abundance Of S P Purpurascensmentioning
confidence: 99%